2017
DOI: 10.1161/circep.116.004662
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Idiopathic Ventricular Arrhythmias

Abstract: Background Ventricular tachycardia (VT) and premature ventricular complexes (PVC) most frequently occur in the context of structural heart disease. However, the burden of idiopathic ventricular arrhythmias (VA) in the general population is unknown. Methods and Results We identified incident cases of idiopathic VA between 2005and 2013 from Olmsted County, MN using the Rochester Epidemiology Project database. For PVC cohorts, we included those with frequent (defined as ≥100 PVC/24 hours) symptomatic PVCs. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 37 publications
2
41
1
2
Order By: Relevance
“…A large study by Latchamsetty et al suggested that male sex may be an independent risk factor for the development of cardiomyopathy. 37,38 Surksha et al found that the incidence of symptomatic PVCs was greater in women, while that of idiopathic ventricular tachycardia was similar among sexes. 39 Considering that asymptomatic status could delay the diagnosis and hence facilitate the development of a cardiomyopathy, women may be less prone to develop cardiomyopathy as they will be treated at an earlier stage.…”
Section: Gendermentioning
confidence: 99%
“…A large study by Latchamsetty et al suggested that male sex may be an independent risk factor for the development of cardiomyopathy. 37,38 Surksha et al found that the incidence of symptomatic PVCs was greater in women, while that of idiopathic ventricular tachycardia was similar among sexes. 39 Considering that asymptomatic status could delay the diagnosis and hence facilitate the development of a cardiomyopathy, women may be less prone to develop cardiomyopathy as they will be treated at an earlier stage.…”
Section: Gendermentioning
confidence: 99%
“…23 With the rise in incidence of idiopathic ventricular arrhythmias, improved survival of patients with heart failure and those with recurrent VT storms or implantable cardioverter defibrillator (ICD) treatments, as well as improved survival in those with coronary artery disease and valvular heart disease, VT ablation rates are likely to continue to rise in the near future. 26,27 There was marked difference in the growth of EP procedure rates in the public and private sector. While the EP procedure rates in the public sector stagnated, the procedure rates in the private sector have doubled.…”
Section: Discussionmentioning
confidence: 99%
“…However, the growth of VT ablations in Australia was 12–18% per year compared to approximately 10% per year in NZ 23 . With the rise in incidence of idiopathic ventricular arrhythmias, improved survival of patients with heart failure and those with recurrent VT storms or implantable cardioverter defibrillator (ICD) treatments, as well as improved survival in those with coronary artery disease and valvular heart disease, VT ablation rates are likely to continue to rise in the near future 26–27 …”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvements in the management of predisposing conditions, especially coronary artery disease (CAD), the incidence of VT has increased when comparing older RCTs where the recurrence rate was 33% to contemporary RCTs which has a recurrence rate between 42%‐45% . In those with idiopathic VT, a recent population‐based study found rates had increased from 12.7 to 16.2 (per 100 000) over a 6‐year period . Paralleling increasing rates of VT is recent local data showing a three‐fold increased rate of ICD implantation over a similar period that incurs significant additional costs on the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In those with idiopathic VT, a recent population-based study found rates had increased from 12.7 to 16.2 (per 100 000) over a 6-year period. 22 Paralleling increasing rates of VT is recent local data showing a three-fold increased rate of ICD implantation over a similar period 3 that incurs significant additional costs on the healthcare system. Certainly, additional strategies are required to reduce rates and healthcare expenditure, of which CA has emerged as a useful adjunctive therapy.…”
Section: Possible Explanations For Temporal Trends In Vt Ablations mentioning
confidence: 99%